The role of secondary data in estimating groundwater levels in the Iberian Peninsula - Nahed Ben-Salem; Amir Rouhani; Nadim K. Copty; Emmanouil A. Varouchakis; J. Jaime Gómez-Hernández; George P. Karatzas; Michael Rode; Seifeddine Jomaa (Groundwater for Sustainable Development, 2026)

Identification of transformation and sources of nitrate in a typical agricultural river of South-Central China using hydrochemistry, multiple isotopes and Bayesian model - Sanyuan Jiang; Wenbo Rao; Tianning Li; Zhijun Song; Ziyi Li; Xiaohui Li; Michael Rode (Journal of Environmental Management, 2026)

Climate change expected to amplify land-use change impacts on nitrogen export from a subtropical catchment in China - Sanyuan Jiang; Adrian D. Werner; Lu Gao; Michael Rode (Journal of Hydrology, 2026)

A framework for selecting Nature-based Solutions: applications and challenges at the catchment scale - Awais Naeem Sarwar; Cristina Caramiello; Francesco Pugliese; Seifeddine Jomaa; Anis Guelmami; Michael Ronse; Pier Paolo Roggero; Nunzio Marrone; Francesco De Paola; Irem Daloglu Cetinkaya; Nadim K. Copty; Michael Rode; et al. (Journal of Environmental Management, 2025)

A review on modelling forest biogeochemistry and the coupled forest – soil interactions in a changing world - Felix Sauke; Rico Fischer; Michael Rode (Environmental Modelling & Software, 2025)

Summer drought enhances diurnal amplitude of CO2 in two German rivers of different size - Peifang Leng; Michael Rode; Matthias Koschorreck (Water Research, 2025)

Direct impact of climate change on groundwater levels in the Iberian Peninsula - Amir Rouhani; Nahed Ben-Salem; Marco D'Oria; Rafael Chávez García Silva; Alberto Viglione; Nadim K. Copty; Michael Rode; David Andrew Barry; J. Jaime Gómez-Hernández; Seifeddine Jomaa (Science of The Total Environment, 2025)

Investigating sediment sources using compound-specific stable isotopes and conventional fingerprinting methods in an agricultural loess catchment - Ghulam Abbas; Seifeddine Jomaa; Patrick Fink; Arlena Brosinsky; Karolina Malgorzata Nowak; Steffen Kümmel; Uwe‐Karsten Schkade; Michael Rode (CATENA, 2024)

The deglacial history of 79N glacier and the Northeast Greenland Ice Stream - David H. Roberts; Timothy P. Lane; Richard S. Jones; Michael J. Bentley; Christopher M. Darvill; Angel Rodes; James A. Smith; Stewart S.R. Jamieson; Brice R. Rea; Derek Fabel; Delia Gheorghiu; Allan Davidson; et al. (Quaternary Science Reviews, 2024)

Advancing river monitoring using image-based techniques: challenges and opportunities - Salvatore Manfreda; Domenico Miglino; Khim Cathleen Saddi; Seifeddine Jomaa; Anette Eltner; Matthew Perks; Salvador Peña-Haro; Thom Bogaard; Tim H.M. van Emmerik; Stefano Mariani; Ian Maddock; Flavia Tauro; et al. (Hydrological Sciences Journal, 2024)

Mapping steady-state groundwater levels in the Mediterranean region: The Iberian Peninsula as a benchmark - Nahed Ben-Salem; Robert Reinecke; Nadim K. Copty; J. Jaime Gómez-Hernández; Emmanouil A. Varouchakis; George P. Karatzas; Michael Rode; Seifeddine Jomaa (Journal of Hydrology, 2023)

System for automated Quality Control (SaQC) to enable traceable and reproducible data streams in environmental science - Lennart Schmidt; David Schäfer; Juliane Geller; Peter Lünenschloss; Bert Palm; Karsten Rinke; Corinna Rebmann; Michael Rode; Jan Bumberger (Environmental Modelling & Software, 2023)

Stream restoration can reduce nitrate levels in agricultural landscapes - Xiangqian Zhou; Seifeddine Jomaa; Xiaoqiang Yang; Ralf Merz; Yanping Wang; Michael Rode (Science of The Total Environment, 2023)

Large-stream nitrate retention patterns shift during droughts: Seasonal to sub-daily insights from high-frequency data-model fusion - Xiaoqiang Yang; Xiaolin Zhang; Daniel Graeber; Robert Hensley; Helen Jarvie; Andreas Lorke; Dietrich Borchardt; Qiongfang Li; Michael Rode (Water Research, 2023)

Factors influencing the establishment of vascular plants at Sphagnum cultivation sites - Amanda Grobe; Michael Rode (Wetlands Ecology and Management, 2023)
Sphagnum cultivation is a type of paludiculture and a way to use formerly drained peatlands productively but under wet and therefore climate-friendly conditions. Where Sphagnum mosses are cultivated other plant species will also establish and possibly compete with the Sphagnum . The aim of this study was to determine which factors influence vascular plant cover as well as plant species numbers at Sphagnum cultivation sites and to derive recommendations for their management. Two cultivation sites were studied in northwest Germany. One of these was established directly after peat extraction while the other was rewetted seven years prior to establishment. Irrigation ditches for water management were installed at both sites. The cover of vascular plants and the number of plant species present were determined in systematically positioned plots. Six variables were tested for their influence on the assessed data by applying boosted regression tree models. The main factors influencing vascular plant cover at the two Sphagnum cultivation sites were the distance to an irrigation ditch (m), the site (location) and Sphagnum cover (%). The number of species per plot was influenced mainly by Sphagnum cover (%), the distance to an irrigation ditch (m) and the donor species used for initiating the cultivation sites. A sufficient supply of nutrient-poor water and optimal Sphagnum growth can reduce vascular plant cover and the number of plant species potentially present at a site. Insufficient water distribution and uneven Sphagnum establishment lead to inhomogeneous site conditions and thus to a higher number of plant species. The number and cover of plant species at a cultivation site are influenced by the vegetation of the sites’ surroundings and the selection of the donor site.

High irradiation and low discharge promote the dominant role of phytoplankton in riverine nutrient dynamics - Norbert Kamjunke; Michael Rode; Martina Baborowski; Julia Vanessa Kunz; Jakob Zehner; Dietrich Borchardt; Markus Weitere (Limnology and Oceanography, 2021)
Rivers play a relevant role in the nutrient turnover during the transport from land to ocean. Here, highly dynamic planktonic processes are more important compared to streams making it necessary to link the dynamics of nutrient turnover to control mechanisms of phytoplankton. We investigated the basic conditions leading to high phytoplankton biomass and corresponding nutrient dynamics in eutrophic, 8th order River Elbe (Germany). In a first step, we performed six Lagrangian sampling campaigns in the lower river section at different hydrological conditions. While nutrient concentrations remained high at low algal densities in autumn and at moderate discharge in summer, high algal concentrations occurred at low discharge in summer. Under these conditions, concentrations of silica and nitrate decreased and rates of nitrate assimilation were high. Soluble reactive phosphorus was depleted and particulate phosphorus increased inversely. Rising molar C:P ratios of seston indicated a phosphorus limitation of phytoplankton, so far rarely observed in eutrophic large rivers. Global radiation combined with mixing depth had a strong predictive power to explain maximum chlorophyll concentration. In a second step, we estimated nutrient turnover exemplarily for N during the campaign with the lowest discharge based on mass balances and metabolism‐based process measurements. Mass balance calculations revealed a total nitrate uptake of 423 mg N m −2 d −1 . Increasing phytoplankton density dominantly explained whole river gross primary production and related assimilatory nutrient uptake. In conclusion, riverine nutrient uptake strongly depends on the growth conditions for phytoplankton, which are favored at high irradiation and low discharge.

Assumptions in ecosystem service assessments: Increasing transparency for conservation - Matthias Schröter; Emilie Crouzat; Lisanne Hölting; Julian Massenberg; Julian Rode; Mario Hanisch; Nadja Kabisch; Julia Palliwoda; Jörg A. Priess; Ralf Seppelt; Michael Beckmann (Ambio, 2021)
Conservation efforts are increasingly supported by ecosystem service assessments. These assessments depend on complex multi-disciplinary methods, and rely on a number of assumptions which reduce complexity. If assumptions are ambiguous or inadequate, misconceptions and misinterpretations may arise when interpreting results of assessments. An interdisciplinary understanding of assumptions in ecosystem service science is needed to provide consistent conservation recommendations. Here, we synthesise and elaborate on 12 prevalent types of assumptions in ecosystem service assessments. These comprise conceptual and ethical foundations of the ecosystem service concept, assumptions on data collection, indication, mapping, and modelling, on socio-economic valuation and value aggregation, as well as about using assessment results for decision-making. We recommend future assessments to increase transparency about assumptions, and to test and validate them and their potential consequences on assessment reliability. This will support the taking up of assessment results in conservation science, policy and practice.

Residual biomass energy potential: perspectives in a peripheral region in Brazil - Ana Pimenta Ribeiro; Michael Rode (Clean Technologies and Environmental Policy, 2019)

Challenges of Reducing Phosphorus Based Water Eutrophication in the Agricultural Landscapes of Northwest Europe - Roland Bol; Gerard Gruau; Per-Erik Mellander; Rémi Dupas; Marianne Bechmann; Eva Skarbøvik; Magdalena Bieroza; Faruk Djodjic; Miriam Glendell; Philip Jordan; Bas Van der Grift; Michael Rode; et al. (Frontiers in Marine Science, 2018)

Improving nitrate load estimates in an agricultural catchment using Event Response Reconstruction - Seifeddine Jomaa; Iyad Aboud; Rémi Dupas; Xiaoqiang Yang; Joachim Rozemeijer; Michael Rode (Environmental Monitoring and Assessment, 2018)

Development of an In Vitro PIV Setup for Preliminary Investigation of the Effects of Aortic Compliance on Flow Patterns and Hemodynamics - Martin Büsen; Christian Arenz; Michael Neidlin; Sam Liao; Thomas Schmitz-Rode; Ulrich Steinseifer; Simon J. Sonntag (Cardiovascular Engineering and Technology, 2017)

Particle Image Velocimetry Used to Qualitatively Validate Computational Fluid Dynamic Simulations in an Oxygenator: A Proof of Concept - Peter C. Schlanstein; Felix Hesselmann; Sebastian V. Jansen; Jeannine Gemsa; Tim A. Kaufmann; Michael Klaas; Dorothee Roggenkamp; Wolfgang Schröder; Thomas Schmitz-Rode; Ulrich Steinseifer; Jutta Arens (Cardiovascular Engineering and Technology, 2015)

Assessment of heavy metals in sediment of Aguamilpa Dam, Mexico - Jesús Gabriel Rangel-Peraza; José de Anda; Fernando A. González-Farías; Michael Rode; Antonio Sanhouse-García; Yaneth A. Bustos-Terrones (Environmental Monitoring and Assessment, 2015)

Decision Support for the Selection of Measures according to the Requirements of the EU Water Framework Directive - Bernd Klauer; Michael Rode; Johannes Schiller; Uwe Franko; Melanie Mewes (Water Resources Management, 2012)

From Desirable Ornamental Plant to Pest to Accepted Addition to the Flora? – the Perception of an Alien Tree Species Through the Centuries - Uwe Starfinger; Ingo Kowarik; Michael Rode; Hartwig Schepker (Biological Invasions, 2003)